2022
DOI: 10.1039/d1mh01019k
|View full text |Cite
|
Sign up to set email alerts
|

Substituent-dependent absorption and fluorescence properties of perylene bisimide radical anions and dianions

Abstract: Perylene-3,4:9,10-bis(dicarboximides) (PBIs) rank among the most important functional dyes and organic semiconductors but only recently their radical anions and dianions attracted interest for a variety of applications. Here, we systematically...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 61 publications
10
72
0
Order By: Relevance
“…In order to unravel the electronic nature of the macrocycles upon electrochemical reduction and oxidation, SEC measurements of the series of macrocycles were conducted in CH 2 Cl 2 (Figure 4c, d/ Figure 5a, b). Reduction of 4T ‐ PBI (Figure 4c, black line) revealed typical spectral signatures of a PBI radical anion (PBI .− , red line) comprising three clearly distinguishable bands at 720 nm, 804 nm and 964 nm corresponding to 4T ‐ PBI .− (red line) which decrease upon further reduction and give rise to a new absorption band at 573 nm belonging to the dianion 4T ‐ PBI 2 − (maroon line) [23] . Spectral shapes of anion and dianion do not change to a great extent within the series of macrocycles because of the decoupled states between D and A as well as the almost identical reduction potentials observed in the CV (Figure S10a, b to Figure S13a, b).…”
Section: Resultsmentioning
confidence: 99%
“…In order to unravel the electronic nature of the macrocycles upon electrochemical reduction and oxidation, SEC measurements of the series of macrocycles were conducted in CH 2 Cl 2 (Figure 4c, d/ Figure 5a, b). Reduction of 4T ‐ PBI (Figure 4c, black line) revealed typical spectral signatures of a PBI radical anion (PBI .− , red line) comprising three clearly distinguishable bands at 720 nm, 804 nm and 964 nm corresponding to 4T ‐ PBI .− (red line) which decrease upon further reduction and give rise to a new absorption band at 573 nm belonging to the dianion 4T ‐ PBI 2 − (maroon line) [23] . Spectral shapes of anion and dianion do not change to a great extent within the series of macrocycles because of the decoupled states between D and A as well as the almost identical reduction potentials observed in the CV (Figure S10a, b to Figure S13a, b).…”
Section: Resultsmentioning
confidence: 99%
“…PDI dianions have remained a surprisingly little explored compound class until now [19] . A handful of prior studies demonstrated that when equipped with PEG chains or phosphonate groups, PDI dianions can be formed efficiently using dithionite as reductant in water [10, 14, 15] .…”
Section: Discussionmentioning
confidence: 99%
“…[43] Conclusion PDI dianions have remained asurprisingly little explored compound class until now. [19] Ah andful of prior studies demonstrated that when equipped with PEG chains or phosphonate groups,P DI dianions can be formed efficiently using dithionite as reductant in water. [10,14,15] One of these studies furthermore demonstrated that PEGylated PDI 2À can luminesce from as inglet-excited state in aqueous solution at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to Ref-PBI (E red,1 = À0.99 V/E red,2 = À1.19 V, Figure S7) these reduction events are at about 0.1 Vm ore negative potential which might be due to amacrocyclic ringstrain induced destabilization of the anionic states that are characterized by ar educed length of the PBI unit along its long axis. [23] Thel ocalization and shapes of the lowest unoccupied and highest occupied molecular orbital (LU-MO/HOMO) of the neutral (5T) 2 -PBI (Figure 2a,b) suggest very little electronic communication between electron donor oligothiophene chain and PBI acceptor segment which is also true for 5T-PBI (Figure S9). Due to the nodes which are located at the imide nitrogen atoms,conjugation of PBI to the residues is interrupted.…”
Section: Redox Propertiesmentioning
confidence: 91%
“…Thes pectral signature for anion and dianion of 5T-PBI depicted in Figure 2e compares well to similar literature known bay-unsubstituted reference PBI structures. [23] Typical spectral PBI signatures comprising three sharp bands at 719 nm, 802 nm and 962 nm corresponding to the anion 5T-PBIC À (Figure 2e,r ed line) which decrease upon further reduction and give rise of ab and at 572 nm (maroon line) belonging to the dianion 5T-PBI 2À .Onefold oxidation of 5T-PBI leads to the simultaneous formation of two peaks at 795 nm and 1480 nm indicating the formation of the cationic species 5TC + -PBI (Figure 2f,b lue line). Further oxidation to the dicationic species 5T 2+ -PBI causes submerging of the afore mentioned cationic signals and emerging of as trong signal at 1043 nm (Figure 2f,v iolet line).…”
Section: Redox Propertiesmentioning
confidence: 99%